Glioblastoma of the cerebellum and brainstem - Stark, Andreas Martin; Maslehaty, Homajoun; Hugo, Heinz Hermann; Mahvash, Mehran; Mehdorn, Hubertus Maximilian (Journal of clinical neuroscience, 2010)
Glioblastoma multiforme (GB) is the most common and most malignant primary intracranial tumor. Of the 577 patients who underwent surgery for newly diagnosed GB (World Health Organization grade IV) between January 1991 and March 2008 at our department, seven had infratentorial GB (iGB) (incidence 1.2%). Patients younger than 21 years of age, as well as patients with gliomatosis cerebri, were excluded from the analysis. We concluded that iGB is rare in adults. Because of its rarity and the non-specific radiological features of iGB, it can easily be misdiagnosed as a brain metastasis, ependymoma or even as a benign lesion such as vestibular schwannoma or meningioma. Surgical removal, or at least stereotactic biopsy, is essential to establish the diagnosis. Postoperative adjuvant therapy similar to that for supratentorial glioblastoma is indicated. We analysed the clinical characteristics and therapy of our patients with iGB and reviewed the literature.